Design and Experimental Implementation of Adaptive Actuator Failure Compensator for Spacecraft Attitude Control Simulator - Somayeh Jamshidi; Mehdi Mirzaei; Maryam Malekzadeh; Sadra Rafatnia (مکانیک هوافضا, 2024)
This study deals with the design and experimental implementation of an adaptive actuator failure compensator for a spacecraft attitude control simulator in the presence of unknown actuator failures and uncertainties. The adaptive actuator failure compensation controller is designed using the backstepping method, which considers uncertainties in the time of occurrence, values, and failure patterns. The adaptive backstepping control method is designed to compensate for the uncertainties of the actuator failure by incorporating the inertia matrix and the distribution matrix. The stability analysis of the proposed adaptive controller for the dynamics of the spacecraft simulator with actuator failures has been carried out. Simulation results and laboratory studies are presented to show the effectiveness of the proposed controller in the presence of stuck, sinusoidal, and complete failures in the spacecraft attitude control simulator system. The results indicate the good performance of the proposed method in the presence of unknown actuator failures and model uncertainties in the system.